Belimumab for systemic lupus erythematosus - Focus on lupus nephritis - Marlene Plüß; Silvia Piantoni; Björn Tampe; Alfred H. J. Kim; Peter Korsten (Taylor & Francis Group, 2022)
In recent years, advances in the treatment and management of patients with systemic lupus erythematosus (SLE) have improved their life expectancy and quality of life. However, lupus nephritis (LN) still represents a major life-threatening complication of the disease. Belimumab (BEL), a fully human monoclonal IgG1λ antibody neutralizing soluble B cell activating factor, was approved more than ten years ago as add-on therapy in adults and pediatric patients with a highly active, autoantibody-positive disease despite standard of care (SoC). Recently, the superiority of the addition of BEL to SoC was also demonstrated in LN. In this review, we provide a comprehensive overview of the study landscape, available therapeutic options for SLE (focusing on BEL in renal and non-renal SLE), and new perspectives in the treatment field of this disease. A personalized treatment approach will likely become available with the advent of novel therapeutic agents for SLE and LN.